Immunochemical analysis of normal and mutant forms of human pyruvate dehydrogenase. - Wicking, C A (1986)
Pyruvate dehydrogenase (PDH) deficiency has been described in many patients with primary lactic acidosis. However, there are very few cases in which a structural defect in the complex has been clearly demonstrated. Measurement of the activity of the PDH complex in cultured human cells has proved unreliable, and a combination of structural and functional studies are required to make a definitive diagnosis. For this reason, an immunochemical strategy has been developed to complement direct enzyme assay in the detection and further characterization of PDH deficiency. We illustrate the usefulness of this approach by describing defects in the alpha-subunit of the pyruvate decarboxylase component of the PDH complex in two patients with primary lactic acidosis. In one patient, there is no immunologically cross-reacting material corresponding to this subunit. In the second patient, there appears to be an intrinsic structural defect in the subunit which restricts dephosphorylation (and hence activation) of the inactive phosphorylated complex.